Photocatalytic Degradation of Methyl Orange in Aqueous TiO2 Suspensions - Niu, P. (Asian Journal of Chemistry, 2012)
The degradation of methyl orange was studied using advanced oxidation process by exposed to UV irradiation in the presence of TiO2. TiO2 or UV light has a negligible effect when used alone. The effect of TiO2 dosage, initial pH of dye solution and the solution area exposed to UV light were studied. It is found that in the investigated range, degradation rate of methyl orange increases with the increase in TiO2 concentration and exposure area of solution. Acidic media is fvaourable to methyl orange degradation. The photodestruction of methyl orange is significantly inhibited by addition of KI as active holes scavenger at pH 2. However, the roles of ·OH and H2O2 are increased gradually as the increase of initial pH value of dye solution.